Avoiding missed diagnosis of mild traumatic brain injury - Bedolla, John (Henry Stewart Talks, 2017)
Traumatic brain injury (TBI), What counts as TBI, What do we fail to diagnose?, Gestalt vs. clinical support tools, Canadian CT head rule (CCHR), CCHR inclusion and exclusion parameters, New Orleans Criteria (NOC), PECARN CT